Ponderomotive effects in magnetospheric hydromagnetic waves (*) - W. Allan (Annales Geophysicae)
The ponderomotive force (PMF) is a ubiquitous nonlinear wave effect arising in plasma physics when applied wave fields or plasma parameters have significant spatial gradients. Some basic properties of the PMF are described as they relate to ULF hydromagnetic waves in the magnetosphere. Examples are given of recent results obtained using both analytical and numerical techniques for waves from the lowest frequencies (determined by the dimensions of the magnetosphere) up to the vicinity of the ion cyclotron frequency. These results include the possibilities that the PMF may transport plasma over large distances in the magnetosphere, and that the PMF may energize magnetospheric ions significantly. In particular the PMF may play a role in transporting and energizing O+ ions from the ionosphere into the body of the magnetosphere. The PMF can also generate nonlinear coupling between the slow magnetosonic mode and the other hydromagnetic modes. This should lead to limitation of density enhancements and, notably in the case of standing Alfvén waves, to spatial harmonic generation, secularly growing frequency shifts, and saturation of driven wave fields. Some implications of these results for the magnetosphere are discussed.